Weaning adult patients with cardiogenic shock on veno-arterial extracorporeal membrane oxygenation by pump-controlled retrograde trial off. (July 2018) - Ling, Lowell; Chan, Kai Man
Background: There is a lack of consensus on the timing of veno-arterial extracorporeal membrane oxygenation (VA-ECMO) liberation. VA-ECMO weaning usually consists of serial decrements until an idling flow is achieved, supported by echocardiographic and haemodynamic assessments. Even with minimal idling flow, right ventricular (RV) preload is reduced and, hence, right heart function is not fully tested under adequate loading conditions. Following the use of a novel technique called Pump Controlled Retrograde Trial Off (PCRTO) in neonate VA-ECMO weaning, we report the use of this technique in seven adult patients on VA-ECMO. Methods: We retrospectively reviewed all adult VA-ECMO patients treated at a tertiary teaching hospital in Hong Kong since 2010. Clinical data, including diagnosis, echocardiography findings, ECMO configuration, PCRTO settings, survival after veno-arterial ECMO (SAVE) score and outcomes, were collected. Mortality and death due to cardiac failure was compared between PCRTO and conventional weaning. Results: Seven patients underwent PCRTO, with a mean SAVE score of -4.4 ± 5.9. All seven patients were successfully decannulated without haemodynamic deterioration. In all cases, no clots or fibrin deposits were found in the circuit after the trial. There was no difference in mean SAVE scores among the seven patients in PCRTO and the 23 patients in the conventional group (-3.6, 95% CI -8.8 to 1.5). The number of deaths due to cardiac failure in the PCRTO group and the conventional group were 0 and 3, respectively (0% vs. 13%, p=0.99). Mortality after decannulation for PCRTO was 42.9% vs. conventional weaning 34.8% (p=0.99). Conclusion: Our study suggests that PCRTO is a simple, safe and reversible alternative weaning method. It may have a particular role in the assessment of patients who have marginal recovery and right heart failure. Prospective controlled studies are needed to establish the potential role of PCRTO in the liberation of patients from VA-ECMO support.